ADVANCE Results: PEG-IFN-β-1a Decreases Disability in RRMS - Hoyle, Brian (MD Conference Express, 2014)
Two-year data from the Efficacy and Safety Study of Peginterferon Beta-1a in Participants With Relapsing Multiple Sclerosis [ADVANCE; NCT00906399; Kieseier BC et al. ECTRIMS 2014 (poster P042)], a study of relapsing-remitting multiple sclerosis (RRMS) in more than 1500 patients, have confirmed the long-term capability of subcutaneously injected peginterferon beta-1a (PEG-IFN-β-1a) in lessening disability progression.